Recruitment of child soldiers in Nepal: Mental health status and risk factors for voluntary participation of youth in armed groups - Kohrt, Brandon A. (Peace Confl, 2016)
Preventing involuntary conscription and voluntary recruitment of youth into armed groups are global human rights priorities. Pathways for self-reported voluntary recruitment and the impact of voluntary recruitment on mental health have received limited attention. The objective of this study was to identify risk factors for voluntarily joining armed groups, as well as the association of conscription status and mental health. In Nepal, interviews were conducted with 258 former child soldiers who participated in a communist (Maoist) revolution. Eighty percent of child soldiers joined ‘voluntarily’. Girls were 2.07 times as likely to join voluntarily (95% CI, 1.03–4.16, p=0.04). Among girls, 51% reported joining voluntarily because of personal connections to people who were members of the armed group, compared to 22% of boys. Other reasons included escaping difficult life situations (36%), inability to achieve other goals in life (28%), and an appealing philosophy of the armed group (32%). Poor economic conditions were more frequently endorsed among boys (22%) than girls (10%). Voluntary conscription was associated with decreased risk for PTSD among boys but not for girls. Interventions to prevent voluntary association with armed groups could benefit from attending to difficulties in daily life, identifying non-violent paths to achieve life goals, and challenging the political philosophy of armed groups. Among boys, addressing economic risk factors may prevent recruitment, and prevention efforts for girls will need to address personal connections to armed groups, as it has important implications for preventing recruitment through new methods, such as social media.